1959
DOI: 10.1039/jr9590003103
|View full text |Cite
|
Sign up to set email alerts
|

630. The rates of reaction of αα-diphenyl-β-picrylhydrazyl with certain amines and phenols

Abstract: The reactions of primary arylamines with aa-diphenyl-p-picrylhydrazyl in carbon tetrachloride have been found to obey the third-order law :Rate of disappearance of hydrazyl = k,[Hydra~yl]~[Aniline] A number of other amines and phenols gave a second-order reaction with the hydrazyl. Alcohols and t-butylamine did not, however, react a t an appreciable rate. The effects of substituents on the reaction with phenols are similar to their effects on reactions in which a carbonium ion is formed adjacent to a phenyl ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
9

Year Published

1960
1960
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 0 publications
1
33
0
9
Order By: Relevance
“…Reaction [7] may possibly be an example of this phenomenon. Similarly, the fact that reaction [15] definitely follows u+ constants whereas reactions [13] and [14] tend more to favor a constants would also be in line with this suggestion.…”
Section: '749supporting
confidence: 72%
“…Reaction [7] may possibly be an example of this phenomenon. Similarly, the fact that reaction [15] definitely follows u+ constants whereas reactions [13] and [14] tend more to favor a constants would also be in line with this suggestion.…”
Section: '749supporting
confidence: 72%
“…[25]. ANTIRADICAL ACTION DPPH • quenching reactions have been used to elucidate structural effects on chemical mechanisms and reactivity of simple phenols since the late 1950s [26][27][28][29]. Antioxidant activity assays for complex polyphenols were initiated in a 1985 pivotal study in which Wayner et al used the water-soluble azide azobis (2-amidinopropane hydrochloride) to generate radicals in plasma, then followed inhibition of oxygen consumption to investigate compounds contributing to antioxidant capacity [30].…”
Section: Figmentioning
confidence: 99%
“…Natural antioxidant capacity/activity 975 3.5 DPPH assays 3.5.1 Experimental approach DPPH is a stable radical with a deep purple colour whose reaction with other radicals, reducing agents, or compounds capable of HAT leads to loss of colour at 515 nm and loss of its electron paramagnetic resonance (EPR) free radical signal [26,29]. Like ABTS +• , DPPH • reacts with both electron and hydrogen donors [75,76], though more slowly, and steric accessibility to the radical site is a clear issue [27,28]. No antioxidant assay is simpler or less expensive to run than the DPPH assay, which accounts for its popularity and extensive use.…”
mentioning
confidence: 99%
“…More recently it has been shown that DPPH can abstract hydrogen from aliphatic thiols (2), aromatic amines (3), and phenols (4,5). The rate constants for the overall disappearance of DPPH vary markedly with the type of X-H bond and, in the case of phenols, with the substituents in the ring.…”
Section: Introductionmentioning
confidence: 99%